Colonization and phytoremediation potential for Miscanthus sacchariflorus in copper tailings - Xin, Jianpan (Environmental technology, 2024)
A pot experiment was conducted to explore the effects of copper (Cu) tailings with various proportions in the substrate on seed germination and morphological traits of the plant. Concurrently, to identify the adaptive and tolerance strategies of the plant to Cu tailings, the uptake and accumulation of the plant to heavy metals, variations in soil enzymatic activities, and metal speciation in the blank, rhizospheric, and non-rhizospheric soils were estimated. Cu tailings at 25% proportion in the substrate exerted no significant negative effects on seed germination and seedling growth. However, Cu tailings at higher proportions (≧50%) inhibited seed germination and disturbed the plant physiological metabolism and growth. More biomass allocated to the plant roots could contribute to more heavy metals being immobilized, arresting their translocation from roots to shoots. This was accepted as a crucial defense mechanism for the plant against heavy metal co-contamination. The plant can improve the biological properties of Cu tailings in terms of enhanced invertase and phosphatase activities. And in turn, this can effectively alleviate heavy metal phytotoxicity. Simultaneously, it markedly decreased exchangeable Cu and Zn content in the rhizosphere in 25% Cu tailings treatments. In 50% Cu tailings treatment, no differences were observed in Zn speciation between rhizosphere and non-rhizosphere soils. In 75% Cu tailings, compared to the non-rhizosphere, an obvious reduction in exchangeable Cu in rhizosphere occurred, while an opposite tendency was demonstrated in carbonate-bound Zn. The plant could successfully colonize in Cu tailings, and represent a phytoremediation potential in Cu tailings